Experience with a Double-Lumen Central Venous Catheter for Hemodialysis - Jones, Terry R. (1987)
We reviewed retrospectively our experience with the transcutaneous placement of 77 double-lumen hemodialysis catheters in the jugular or subclavian veins in 65 patients. The catheters remained in place for an average of 20.7 days. Three unrelated deaths occurred within 30 days of insertion. Post-insertion chest roentgenograms were made on all patients. One pneumothorax and one misplacement into the carotid artery were noted. Five patients developed blood-culture-substantiated sepsis that required hospitalization. Deep-vein thrombosis occurred in one patient and subclavian-vein stenosis was found in two other patients. Various mechanical difficulties such as kinking, cracking, and thrombosis were encountered. The use of this catheter provides immediate access for hemodialysis with a minimum of complications. However, its disadvantages include its length, tendency to kink, and the requirement for a separate venous cannula to be used with each hemodialysis. (Texas Heart Institute Journal 1987; 14:307-311)